Herbal Supplement of Phaseolus vulgarisL Beans in Metabolic Abnormalities Induced by Atypical Antipsychotics A Review - Pawar, Amit (International Journal of Pharmaceutical & Biological Archive, 2013)
Herbal Supplement of Phaseolus vulgarisL Beans in Metabolic Abnormalities Induced by Atypical Antipsychotics A Review